Fertilizer and Soil Solubility of Secondary P Sources-The Estimation of Their Applicability to Agricultural Soils - Václavková, Šárka; Šyc, Michal; Moško, Jaroslav; Pohořelý, Michael; Svoboda, Karel (Environmental science & technology, 2018)
The demand for phosphorus (P) sources is increasing with the growing world population, while objections to direct agricultural use of waste P sources, such as sewage sludge, are being raised. Therefore, the need arises to employ safe and efficient secondary P fertilizer sources, originating from P-rich wastes. These recycling sources are commonly tested in accordance with the current fertilizer rules, designed originally for conventional apatite-based P fertilizers. The behavior of sewage sludge ash, an inorganic recycling secondary P source, was investigated under soil-like conditions. Standardized soil P tests, including the soil buffering capacity test and the Olsen, the Mehlich3, and water extraction methods, were employed together with standardized fertilizer P-solubility tests by neutral ammonium citrate and 2% citric acid extraction. In addition, total content and the overall soil mobility of selected metallic elements present in sewage sludge ash were investigated. The suitability of standardized soil tests for the evaluation of recycling P sources was shown. An apparent influence of Ca:Al content ratio on sewage sludge ash behavior under different soil-like conditions shows the inadequacy of the current fertilizer test and the necessity to understand soil-like behavior of secondary P sources, when considering these as possible agricultural P bearers (fertilizers).
Keywords: Fertilizers; Agriculture; Sewage; rozpustnost; Phosphorus; Solubility; odpadní vody; půda; fosfor; Soil; zemědělství; průmyslová hnojiva